Waiting for answer This question has not been answered yet. You can hire a professional tutor to get the answer.

# t1 = x b. t2 = (y. t3 = (x.(x y)) d. t4 = ((x.y) x) e. t5 = y.wyzx d. t6 = x. t7 = ((((x.x)z)x)(( y.

a. t1 = x

b. t2 = (λy.y)

c. t3 = (λx.(x y))

d. t4 = ((λx.y) x)

e. t5 = λy.w λw.wyzx

d. t6 = λx.xz λy.xy

f. t7 = ((((λx.x)z)x)(( λy.(z y))y))

Using the terms from above, apply the following substitutions and show the resulting expression:

a. t1[x := t2]

b. t2[y := 5]

c. t4[x := t3]

d. t6[y := t5]

e. t7[z := t2]